The Emerging Roles of Circ-ABCB10 in Cancer - Huang, Zhenjun; Shan, Renfeng; Wen, Wu; Li, Jianfeng; Zeng, Xiaohong; Wan, Renhua (Frontiers in Cell and Developmental Biology, 2022)
Circular RNAs (circRNAs) are non-coding RNAs (ncRNAs) without 5’ caps and 3’ tails, which are formed from precursor mRNAs (pre-mRNAs) being inversely back spliced by exons. circRNAs are characterized by covalently closed loop structure, and are abundantly expressed in eukaryotic cells. With the development of RNA sequencing, it has been found that circRNAs exist in the regulation of numerous human diseases and are related to the occurrence, development and prognosis of diseases. Studies on various tumors have revealed that circRNAs have both positive and negative effects on the occurrence and development of tumors. Circ-ABCB10, a circular RNA originating from exons of ABCB10 located on chromosome 1q42, has been proved to play an important role in different cancers. Here, we primarily introduce the role of circABCB10 in cancer and clearly formulate its influences and functions to cancer’s process, in which it gives us a wide range of cognition of circABCB10. Thus, this article aims to generalize the circABCB10 biological functions in the diagnosis and treatment of different tumors and its related miRNA genes. In this way, we wish to have a sufficient understanding and discover the future development direction of circABCB10